Incarnation and Redemption in the Light of Theotokos’ Icon - Chochev, Georgi (Forum Theologicum Sardicense, 2025)
Incarnation and Redemption in the Light of Theotokos' Icon. In the icon of Theotokos, one can find answers to two very important questions. The first reflects the incarnation of the Word, while the second reflects its consequences. The incarnation and redemption depicted in the icon of the Virgin are indivisible. The image of Theotokos reveals the true incarnation of the Second Person of the Holy Trinity. The Kontakion of the day demonstrates that the doctrine of Christ and His Mother are inseparable and that she is the one who received Christ into her womb, becoming the dwelling place of the Incompatible. In her, the boundaries between the visible and invisible, between heaven and earth, and between God and man have been transcended. Keywords: Virgin Mery, Theotokos, Incarnation, Redemption, Iconography, Orthodox Dogmatics